An experimental investigation of the mechanism and mitigation measures for the coil spring fracture of a locomotive. (May 2022) - Wang, Kaiyun; Yang, Yifan; Yang, Yunfan; Xu, Mingkun; Chen, Shiqian; Ling, Liang; Xiao, Feixiong; Zhang, Kailin; Ma, Chengxiang
Highlights: The potential factor of the coil spring fracture is discovered by field surveys. A well-designed modal test is performed to obtain the modal frequency of the coil spring. The dynamic stress of the coil spring is measured to validate the structural resonance. Two available countermeasures are proposed to mitigate the coil spring fracture. Abstract: The fracture of coil springs occasionally appears in rail vehicles, which may severely jeopardise the train running safety. In this study, the fracture phenomenon of the locomotive coil spring is investigated mainly using the experimental methods. Field surveys are preliminarily carried out, including statistical analysis, visual observations, material properties tests, and measurement of the wheel out-of-roundness (OOR), all of which can help to discover the potential contributing factors to the coil spring fracture. To ascertain the root cause of the coil spring fracture, a well-designed modal test is carried out to determine the natural frequency of the coil spring. The dynamic stress of the coil spring is also measured to verify whether the structural resonance existed. Moreover, dynamic simulation is performed to reproduce the resonance phenomenon. The experimental results show that the 1st expansion modal of the coil spring will be motivated by the excitation frequency of the 17th order wheel OOR if the locomotive runs frequently in the speed of 75–80 km/h. Two mitigation measures are presented, including the wheel re-profiling and structure optimization for the coil spring. Furthermore, the proposed countermeasures are proved to be effective for reducing the risk of coil spring fracture according to the filed tracking tests.